2012
DOI: 10.1007/s11013-012-9277-8
|View full text |Cite
|
Sign up to set email alerts
|

Explanatory Models of Female Pubertal Timing: Discordances Between Cultural Models of Maturation and the Recollection and Interpretation of Personal Developmental Experiences

Abstract: Given the ambiguity surrounding the source of the continuing trend toward earlier menarche observed in Westernized nations, several competing explanatory models have emerged regarding variation in pubertal timing. While a biomedical model proposes that predominantly constitutional characteristics shape the maturation timetable, an alternative framework derived from Life History Theory (LHT) evolutionary principles emphasizes the influence of psychosocial factors on development. Working with a sample of women 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…The mediating effects of perceived stress in the relationship between father absence and early onset of menarche suggest the possible presence of a causal sequence whereby father absence is a risk factor for the initial perception of familial or psychosocial stress by the child and subsequent early onset of menarche. These findings are consistent with the theoretical underpinnings of stressful circumstances that predict earlier reproductive development (Belsky et al, 1991 ; Ellis et al, 2003 ; Tither and Ellis, 2008 ; Buzney and Decaro, 2012 ). Performing subgroup analyses of various sources of stress affecting menarcheal timing and longitudinal testing for the aforementioned causal sequence are key directions for future research.…”
Section: Discussionsupporting
confidence: 85%
“…The mediating effects of perceived stress in the relationship between father absence and early onset of menarche suggest the possible presence of a causal sequence whereby father absence is a risk factor for the initial perception of familial or psychosocial stress by the child and subsequent early onset of menarche. These findings are consistent with the theoretical underpinnings of stressful circumstances that predict earlier reproductive development (Belsky et al, 1991 ; Ellis et al, 2003 ; Tither and Ellis, 2008 ; Buzney and Decaro, 2012 ). Performing subgroup analyses of various sources of stress affecting menarcheal timing and longitudinal testing for the aforementioned causal sequence are key directions for future research.…”
Section: Discussionsupporting
confidence: 85%
“…Finally, a small psychological literature suggests that this question merits further investigation in humans. Several studies have linked childhood stressors to earlier age at menarche, suggesting that early exposure to stress could program an accelerated reproductive trajectory in females, though we know of no studies that have looked at early exposure to stress in relation to reproductive function or success past menarche (Belsky et al, 1991, Buzney and DeCaro, 2012, Ellis and Garber, 2000, Wierson et al, 1993). Similarly, we know of no studies that have examined prenatal stress in relation to timing of reproductive trajectories, however the question merits further study.…”
Section: Discussionmentioning
confidence: 99%
“…The stimulation of the ears and eyes subsequently stimulates the reproductive and genital systems to accelerate genital maturation. The study conducted by Buzney & DeCaro (2012) also found psychosocial factors affected the age of menarche, which included access to westernised content. In an earlier study, it was stated that the linkage between pornographic media exposure accelerated puberty in adolescents which then indirectly leads to an earlier age of menarche (Ayuningtyas, 2013).…”
Section: Discussionmentioning
confidence: 97%